Impact of the COVID-19 pandemic on healthcare workers - Prasad, Versha (International Journal of Research in Medical Sciences, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has heavily burdened, and in many cases overwhelmed, healthcare systems including healthcare workers. The novel COVID-19 started from Wuhan in mainland China. Since then it has affected most of the nations and continents because of its rapid spread. Most commonly affected are the healthcare professionals who are working on the frontline. The COVID-19 epidemic has mushroomed globally, disrupting the existence of millions It is a generalized mental condition occurring without any trigger or stimulus. Various symptoms of depression are: anxious, sad and empty feelings, hopelessness, guilt and may be sense of helplessness, restless attitude, irritation, and lack of interest in various hobbies and activities and were once considered relax able and which are used to provide pleasure. Furthermore, healthcare workers reported mental health problems putatively associated with healthcare workers’ occupational activities during and up until years after epidemics, including symptoms of post-traumatic stress, burnout, depression and anxiety. As for lack of material, a high percentage of professionals are getting infected for not having adequate personal protection equipment (PPE) and not using it properly, having to re-use in many occasions equipment which is only recommended for one-time utilization. During work performed by healthcare workers, several pressure elements from different sources may impact on keeping optimal conditions for a healthy working environment, and because of the saturation of the sanitary facilities due to the high level of virus infection, the health of these professionals has been obviously affected. While the main focus is concentrated on laboratory testing, finding the disease cure and prevention of transmission, all individuals are undergoing a plethora of psychological problems while adjusting to current lifestyles and disease fear. In current study, an attempt has been made to find out the impact of this pandemic situation on psychological well-being of healthcare and non-healthcare workers. Our study has reported identical findings to those reported by numerous investigators working across the globe. The present paper has outlined the stressors which the frontline health care professionals have faced including fear of spreading disease to co-workers and members of the family, irregular sleep patterns, abrupt work cycles, and lack of adequate training skills in dealing with such a novel situation.